PENGEMBANGAN MODUL ELEKTRONIK BERBASIS SMARTPHONE BERPLATFORM ANDROID PADA MATAKULIAH TAKSONOMI TUMBUHAN TINGGI - Herdiyana Fitriani; Hunaepi Hunaepi (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: Module is a tool that is intended for self-study. In this era of technological advances, modules or learning aids are needed in the learning process. These technological advances provide great opportunities for lecturers to be able to present the learning media in mobile version format such as electronic module. This study aims to: (1) produce electronic module products based on smartphone platform android on high taxonomic taxonomy; (2) find out the feasibility of electronic module based on smartphone platform android as a learning material in high taxonomic taxonomy; (3) to know the effectiveness of electronic module availability of smartphones based on android platform as a learning material in high plant taxonomy course. The research design used refers to the modified development research design of the 4D development model of Thiagarajan. The procedures include 4 stages: (1) defining (define), (2) design, (3) development, (4) disseminate the testing phase and product revision. Expert Validation results on electronic modules android platform developed analyzed descriptively quantitative-qualitative with the overall result of 3.5 with good category. Peritem validation results: (1) Validity of electronic module with android plates on the material aspect of 3.4 with good category; (2) Validity of electronic module with android plates on the presentation aspect of 3.6 with good category; and (3) The validity of electronic module with android plates on the language aspect of 3.6 with good category. The student response result shows that, electronic platform android platform is a new teaching material for students and can help or facilitate the students to understand the taught material, and train student self-reliance. The effectiveness of the module is seen from the level of understanding of student concepts that can be stated that the average understanding of student concepts is at the relational level, with the percentage of 45.67%, and the average score change in student concept understanding before and after learning of 0.57 (categorized medium). Based on these data can be seen that the electronic module android platform that has been applied can be declared effective or have an impact or influence on understanding the concept of students. The conclusions of this study are electronic modules android platforms declared eligible for use in the course of Taxonomy of High Level Plants.